Risk of non-hypoglycemic agents for hypoglycemia-related hospitalization in patients with type 2 diabetes: a large-scale medical receipt database analysis. Issue 2 (21st April 2023) - Horii, Takeshi; Otsuka, Mai; Yasu, Takeo
Abstract : Introduction: Hypoglycemia is listed as an adverse effect in the package inserts of not only hypoglycemic agents but also many other drugs. We aimed to clarify real-world factors related to an increased risk of hypoglycemia-related hospitalization (HRH) in Japanese patients with type 2 diabetes (T2D) on non-hypoglycemic agents that have been associated with hypoglycemia. Research design and methods: This cross-sectional study was performed using data from the Medical Data Vision administrative claims database. We identified patients with T2D who were enrolled in the database between April 2014 and October 2019. Logistic regression analyses were performed to identify clinical factors associated with HRH due to non-hypoglycemic agents. Results: Among 703 745 patients with T2D, 10 376 patients (1.47%) experienced HRH. The use of 332 non-hypoglycemic agents was associated with hypoglycemia. Multivariate analysis was performed to calculate OR for HRH. Seventy-five drugs had an OR greater than 1, and the values were significant. The OR was the highest for diazoxide (OR 15.5, 95% CI 4.87 to 49.3). The OR was higher than 2.0 for methylphenidate (OR 5.15, 95% CI 1.53 to 17.3), disulfiram (OR 4.21, 95% CI 2.05 to 8.62) and hydrocortisone (OR 2.89, 95% CI 1.11 to 7.51). Conclusion: This large retrospective analysis revealed that the risk of HRH from some non-hypoglycemic agents in patients with T2D may be increased. The results of this study are expected to support treatment planning by physicians and healthcare professionals involved in diabetes care.